The Effect of Firm Characteristics on the Disclosure of IAS/IFRS Information: The Cases of Tunisia, France and Canada - Hedi Baazaoui; Mohamed Ali Zaraï (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2019)
The effect of firm characteristics on the disclosure of IAS/IFRS information can not be studied in isolation of the national context of the country of nationality or domicile of the firm. Starting from the assumption that the intrinsic characteristics of the firm depend significantly on its size and the country of his nationality, we chose to work on companies belonging to different trading indices and from countries with different cultures and levels of economic development. The selected countries are Tunisia, France and Canada since Tunisia differs from Canada and France mainly by the level of economic development (developing countries) and France differs from Canada by culture. Our sample includes 52 Tunisian companies (40 listed on the first market and 12 on the alternative market), 244 French companies (35 CAC40 Index (top 40 French firms) and 209 CACsmall (index of small Capitalization French firms)) and 223 Canadian companies (36 ^TX60 (first 60 Canadian companies) and 187 ^TX20 Index (Small Capitalization Canadian firms)). Our results showed that the determinants of the disclosure of IAS/IFRS information will vary depending on the nationality of the firm and also showed the importance of the nationality of the firm in explaining disclosed information since the proxy used